INFLUENCE OF AN ANTHROPOGENIC FACTOR ON THE GEOECOLOGICAL CONDITION OF CITIES (ON THE EXAMPLE OF FERGANA-MARGILAN AGGLOMERATION) (Scientific journal of the Fergana State University, 2024)
This article explains the causes of environmental problems in some cities of Uzbekistan, as well as in major cities around the world. These processes are explained using the example of the Fergana-Margilan agglomeration emerging in our country. A partial assessment of the geo-ecological situation that has developed as a result of increasing population density and the increase in medium and small industrial enterprises in the territory of these two cities is given. Possible ways to optimize the influence of the anthropogenic factor, which is the main cause of these problems, are also shown.